ANALISIS FAKTOR YANG MEMPENGARUHI EKSISTENSI RITEL TRADISIONAL DALAM MENGHADAPI RITEL MODERN DI KECAMATAN MEDAN AMPLAS - Muflihatul Fauza (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
The aim of this study to determine the factors affecting the existence of traditional retail and the dominant factor affecting the existence of traditional retail in Medan Amplas. The research sample 100 respondents, the research method used is quantitative approach using path analysis and using SPSS version 16, LISREL version 8.8 and MSI excel program. Results of this study, the factors that influence to the purchasing decision is the price factor with the t value 3,34, while the factor of produk and place does not affect to purchasing decision. And the factors that influence directly to existence of traditional retail are produk, price and purchase decision factor, while the place do not effect it directly. And indirect effect of the existence of traditional retail through the purchase decision are the produk and price factor with t-value 4,88 and 2,44 is greater than t table 1,97.